EPISTEMOLOGI IDEOLOGI KEAMANAN PANGAN - Yusuf Adiwibowo (Universitas Airlangga, 2016)
Food safety issues have a significant impact on the socio-economic life of this world, which is characterized by the global spread of the virus hazards, microbial pathogens and pesticide residues that cause health problems and even death. In order to protect the state from the threat of viral, microbial pathogens and pesticide residues, the developed states apply the standards for the trade barriers so that the hazardous contaminated products can be prevented to enter to their states. Islamic Epistemology describes the food security in Qur'an as Surat Al-Baqoroh paragraph 2: 168